RANCANGAN BETON NORMAL DAN BETON SERAT ROVING DENGAN PASIR TANAH MERAH SERTA BATU PECAH KUTAI BARAT - Mallita, Meditatsyo (KURVA S JURNAL MAHASISWA, 2014)
Final Project Faculty of Civil Engineering Department of the University of August 17th1945 Samarinda.Normal concrete is concrete that has a weight of 2200 - 2500 kg/m³ using naturalaggregates were broken or without broken.Fiber-reinforced concrete is a mixture of concrete plus fiber, generally in the form ofrods with a size of 5-500 μm with a length of about 25 mm. Fiber material may be asbestos fibers,plastic fibers (polypropylene), or a piece of steel wire. The fibers in concrete prevents cracks thatmakes concrete more ductile than ordinary concrete. The purpose of this study was to compare thecompressive strength value produced normal concrete and fiber-reinforced concrete that usescoarse crushed aggregate of Kampung Keay Kutai Barat and fine aggregate from Tanah MerahNorth Samarinda.This study uses a mix design method (Indonesian National Standard) SNI 03-2847-2002conducted in the laboratory using the maximum size of coarse aggregate is 40 mm. The sampleused for normal concrete or concrete fiber rovings variation of 0.25% and a variation of 0.5%respectively using 30 samples and the total number of samples is 90 samples.iiFrom the test results normal concrete compressive strength at 28 days averagecompressive strength value necessary (f'cr) is 108.050 Kg/cm² and compressive strength implied(f'c) is 87.987 Kg/cm2 of the average compressive strength necessary that targeted (f'cr) = 255kg/cm² and the compressive strength implied (f'c) = 175 kg/cm². Concrete compressive strengthtesting of fiber rovings proportion of 0.25% at 28 days the value of the average compressivestrength of the targeted (f'cr) was 120.49 kg/cm² and the compressive strength implied (f'c) was102.42 kg/cm² of the average compressive strength needs to be targeted (f'cr) = 255 kg/cm² andthe compressive strength implied (f'c) = 175 kg/cm². Concrete compressive strength testing of fiberrovings proportion of 0.5% at 28 days the compressive strength average (f'cr) was 114.58 kg/cm²and the compressive strength implied (f'c) is 93.68 kg/cm² of the average compressive strengthneeds to be targeted (f'cr) = 255 kg/cm² and the compressive strength implied (f'c) = 175 kg/cm².